FACTORS OF ORGANIZING INCLUSIVE TEACHING AND ITS PEDAGOGICAL AND PSYCHOLOGICAL SAFETY IN CONTINUING EDUCATION - Kobilova Shaxnoza Xudayshukurovna (Modern American Journals, 2025)
Independent learning is a crucial aspect of the modern education system, providing quality educational opportunities for all students, regardless of their abilities or lack thereof. This article examines the pedagogical and psychological safety factors that underpin inclusion in order to enhance effective action in a lifelong learning environment. The findings highlight the importance of creating inclusive learning environments that promote emotional well-being, academic success, and social integration. The study concludes with recommendations for effective educational strategies, institutional policies, and management of the educational environment, including practical inclusion, pedagogical safety, psychological safety, universal design for learning (UDL), differentiated instruction, assistive technologies, lifelong learning, teacher training, and social and emotional support.
Keywords: Inclusive education, inclusive education, pedagogical safety, psychological safety, universal design for learning (UDL), differentiated instruction, assistive technologies, lifelong learning, teacher training, and social and emotional support.